Non-cellular immunotherapies in pediatric central nervous system tumors - Rumler, Sarah (Frontiers in Immunology, 2023)
Central nervous system (CNS) tumors are the second most common type of cancer and the most common cause of cancer death in pediatric patients. New therapies are desperately needed for some of the most malignant of all cancers. Immunotherapy has emerged in the past two decades as an additional avenue to augment/replace traditional therapies (such as chemotherapy, surgery, and radiation therapy). This article first discusses the unique nature of the pediatric CNS immune system and how it interacts with the systemic immune system. It then goes on to review three important and widely studied types of immune therapies: checkpoint inhibitors, vaccines, and radiation therapy, and touches on early studies of antibody-mediated immunogenic therapies, Finally, the article discusses the importance of combination immunotherapy for pediatric CNS tumors, and addresses the neurologic toxicities associated with immunotherapies.